Das configurações histórico-culturais à transculturação narrativa na América latina: o encontro de Darcy Ribeiro e Ángel Rama - Cunha, Roseli Barros (2005)
The present article briefly approaches the importance of the anthropological studies of the Brazilian Darcy Ribeiro in the critical work by Ángel Rama. The interchange between the intellectuals can be perceived in Transculturación narrativa en América Latina (1982a), and it must be understood in a deepened way. However, it is necessary to notice that the confluence between the work of both abready existed. The first meeting occurs in 1964, when the anthropologist was exiled in Montevidéu, and the contact continued in other projects they have undertaken in their studies on the Latin American culture.